Analisis Hubungan Kepatuhan Laporan Keberlanjutan Terhadap Peraturan OJK Dengan Kinerja Perusahaan - Wijaya, Aida; Novianto, Robertus Ary (Owner : Riset dan Jurnal Akuntansi, 2024)
Indonesia entered into Paris Agreement in 2015, which showed the serious intention of the government to commit to the implementation of activities that support sustainability in the environment, and society, as well as good governance. To accelerate the implementation, the Indonesian government encouraged all stakeholders in the society to get involved, starting with issuing Financial Services Authority regulation No.51/OJK.03/2017, with some listed companies as the first target to carry out sustainable activities and prepare the Sustainability Report. This study aims to analyze the relationship between sustainable activities reported in the Sustainability Report as regulated by the Financial Services Authority in the FSA regulation No. 51/OJK.03/2017 and the company’s performance using ROE as proxy. In 2021 Indonesian government issued another regulation, that was the SE OJK no. 16/SEOJK.04/2021 which explained that the sustainability report was inseparable with financial report. The point was that sustainability activity should influence a company’s performance. The population of this research was the listed companies classifed in the consumer non cyclicals sector, from which 30 samples were taken using purposive sampling techniques. Based on statistical testing using the regression method, the result showed that the  Sustainability Report do not have significant influence on the ROE. This condition could mean that the sustainable activities carried out by the companies was not significant enough to influence the performance.